Efektivitas Damar Putih dalam Pelestarian Tanaman Endemik Plasma Nutfah Oleh PT Pertamina Patra Niaga DPPU SMB II di Kota Palembang - Ahmad Apriyadi; Ayu Nirmala Lutfie Syarief; Rada Aprilia; Shinta Dwi Maharani (Jurnal Syntax Admiration, 2023)
This research aims to describe the effectiveness of damar putih (white resin) in conserving endemic germplasm plants by PT Pertamina Patra Niaga DPPU Sultan Mahmud Badaruddin II Palembang. The study was conducted through a survey method at the Punti Kayu Palembang Tourist Park located at JL. Kol. H. Burlian, Srijaya, Alang-alang Lebar District, Palembang City, South Sumatra, 30151. Based on the Minister of Forestry Decree dated March 7, 1985 No. 57/Kpts-II/1985, the Punti Kayu Forest area was designated as a tourist forest that serves as the lungs of the city. On October 7, 2002, the Minister of Forestry through Decree No. 9273/Kpts-II/2002 designated Punti Kayu as a conservation forest with a function as a Natural Tourist Park covering an area of ​​39.9 hectares. This research was conducted in July 2023. Based on the study, there was an increase in the number of protected flora, particularly supported by PT Pertamina Patra Niaga DPPU SMB II, with a total of 1,668 trees. In 2023, the data for planting trees of the rare endemic biodiversity of South Sumatra, including damar putih, increased to 2,650 trees/seeds, showing a yearly improvement. This indicates that the planting of trees and the conservation of endemic germplasm, specifically damar putih, are effectively implemented.